18F-FLUORODEOXYGLUCOSE POSITRON EMISSION TOMOGRAPHY IN CANCER PATIENTS: A WHOLE-BODY EXAMINATION PROCEDURE - O. V. Mukhortova; I. P. Aslanidi; L. A. Ashrafyan; I. V. Shurupova; E. P. Derevyanko; T. A. Katunina; D. B. Alimardonov; A. V. Ulyanova (Опухоли женской репродуктивной системы, 2014)
Positron emission tomography (PET) is one of the current techniques of molecular radionuclide imaging, which provides a qualitative and quantitative assessment of biochemical processes occurring in a living organism. The paper contains information on how to per- form 18F-fluorodeoxyglucose PET for whole-body examination. It analyzes factors that influence the accuracy of obtained results, methods for PET image analysis, and reasons for possible diagnostic errors.